Pengaruh Dana Desa Dan Alokasi Dana Gampong Terhadap Kemiskinan Di Kecamatan Makmur Kabupaten Bireuen - Aida Fitri; Khairil Anwar (Jurnal Ekonomi Regional Unimal, 2020)
This study aims to determine how much Influence funds and village fund allocation have on poverty in Makmur District, Bireuen Regency. This study uses the panel data analysis method. Which is a combination of time-series data from 2015 to 2019, and a cross-section involving 27 villages and results in 135 observations. The results show that village funds have a negative and significant effect on poverty in the Makmur sub-district. Meanwhile, the allocation of village fund has no significant effect on poverty in the Makmur sub-district.Keywords:Village Fund, VillageFund Allocation, Poverty.